Facing value radical perspectives from the arts - Lauwaert, Maaike 1978-; Westrenen, Francien van (Valiz, 2017)
About the imaginative re-use of materials, and value creation by artists, designers and architects, with source texts, new texts and images
Keywords: Kunst; Wertschöpfung; Künstler; Recycling; Aufsatzsammlung